2019
DOI: 10.1111/bjh.15772
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of mature (non‐anaplastic) T‐ and NK‐cell lymphomas in childhood, adolescents, and young adults

Abstract: Paediatric non-Hodgkin lymphomas (pNHL) are a diverse group of malignancies characterised by nodal and/or extranodal involvement. Less common pNHL forms include those derived from mature T-and natural killer (NK) cells. Much of our current understanding of paediatric mature (non-anaplastic) T/NK-cell lymphomas with respect to pathogenesis, diagnosis and treatment is extrapolated from adult literature. At the Sixth International Symposium on Childhood, Adolescent and Young Adult Non-Hodgkin Lymphoma, convened S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…These are both histone deacetylase inhibitors with encouraging results from clinical trials; however, in a single-institutional study of 4 pediatric patients with multiple relapsed/refractory PTCL, romidepsin was unsuccesful. 20,21 There are numerous other agents that are still under investigation in clinical or preclinical trials to determine their utility in PTCL. Nivolumab, the anti-PD1 antibody FDA approved for the treatment of relapsed and refractory Hodgkin's lymphoma, shows potential after a phase I study reported objective response rate of 40% in adults with PTCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are both histone deacetylase inhibitors with encouraging results from clinical trials; however, in a single-institutional study of 4 pediatric patients with multiple relapsed/refractory PTCL, romidepsin was unsuccesful. 20,21 There are numerous other agents that are still under investigation in clinical or preclinical trials to determine their utility in PTCL. Nivolumab, the anti-PD1 antibody FDA approved for the treatment of relapsed and refractory Hodgkin's lymphoma, shows potential after a phase I study reported objective response rate of 40% in adults with PTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Romidepsin and belinostat are also both FDA approved for relapsed and refractory PTCL in the adult population. These are both histone deacetylase inhibitors with encouraging results from clinical trials; however, in a single-institutional study of 4 pediatric patients with multiple relapsed/refractory PTCL, romidepsin was unsuccesful 20,21…”
Section: Discussionmentioning
confidence: 99%